Selenium and Selenoproteins in Gut Inflammation-A Review - Shaneice K. Nettleford; K. Sandeep Prabhu (MDPI AG, 2018)
Inflammatory bowel disease (IBD), characterized by severe flares and remissions, is a debilitating condition. While the etiology is unknown, many immune cells, such as macrophages, T cells and innate lymphoid cells, are implicated in the pathogenesis of the disease. Previous studies have shown the ability of micronutrient selenium (Se) and selenoproteins to impact inflammatory signaling pathways implicated in the pathogenesis of the disease. In particular, two transcription factors, nuclear factor-κB (NF-κB), and peroxisome proliferator activated receptor (PPAR)γ, which are involved in the activation of immune cells, and are also implicated in various stages of inflammation and resolution, respectively, are impacted by Se status. Available therapies for IBD produce detrimental side effects, resulting in the need for alternative therapies. Here, we review the current understanding of the role of NF-κB and PPARγ in the activation of immune cells during IBD, and how Se and selenoproteins modulate effective resolution of inflammation to be considered as a promising alternative to treat IBD.